2016
DOI: 10.1177/1363461516660901
|View full text |Cite
|
Sign up to set email alerts
|

How patients and clinicians make meaning of physical suffering in mental health evaluations

Abstract: Clinicians in community mental health settings frequently evaluate individuals suffering from physical health problems. How patients make meaning of such "comorbidity" can affect mental health in ways that may be influenced by cultural expectations and by the responses of clinicians, with implications for delivering culturally sensitive care. A sample of 30 adult mental health intakes exemplifying physical illness assessment was identified from a larger study of patient-provider communication. The recordings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 33 publications
0
23
1
Order By: Relevance
“…It contradicts an earlier study by Carson, Katz, and Alegría (2016) on physical co-morbidity in mental health patients, which reported that patients perceived limitations on their sense of agency due to their experience of physical illness. It is possible that psychiatric co-morbidity has a different impact on a patient's sense of agency but further research is needed to confirm this and to understand the reasons behind it.…”
Section: Internal Locus Of Controlcontrasting
confidence: 91%
“…It contradicts an earlier study by Carson, Katz, and Alegría (2016) on physical co-morbidity in mental health patients, which reported that patients perceived limitations on their sense of agency due to their experience of physical illness. It is possible that psychiatric co-morbidity has a different impact on a patient's sense of agency but further research is needed to confirm this and to understand the reasons behind it.…”
Section: Internal Locus Of Controlcontrasting
confidence: 91%
“…We found one article with quantitative design (see Table 1) (Dezutter et al, 2016), one employing a mixed methods design (Zander et al, 2015) and two using a qualitative approach (Bullington, Nordemar, Nordemar, & Sjostrom-Flanagan, 2003; Carson, Katz, & Alegría, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We found one article with quantitative design (see Table 1) (Dezutter et al, 2016), one employing a mixed methods design (Zander et al, 2015) and two using a qualitative approach (Bullington, Nordemar, Nordemar, & Sjostrom-Flanagan, 2003;Carson, Katz, & Alegría, 2016). The quantitative study was from Belgium (Dezutter et al, 2016), analysing patients' experiences of the doctor-patient communication and their satisfaction with the attention given to the impact of pain on their meaning in life by the treatment teams or medical doctors.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations